Fotos de Roberto H. Todd (Copias) - Todd, Roberto H. (My University, 2015)
Copias de las fotos de Roberto H. Todd en mejores condiciones. Documento RT-4-001
Keywords: Henna, José Julio, 1848-1924; Diaz Albertini, Ricardo; Rubens, Horacio; Hostos, Eugenio María de, 1839-1903; Villalón, José Ramón; Zeno Gandía, Manuel, 1855-1930; Barceló, Antonio R., 1868-1938; Rossy y Calderón, Manuel F., 1861-1932; López Sicardo, Rafael, 1875-1937; Valdés, Ramón; Asenjo, Conrado; Fajardo Cardona, Pascasio; Rosalí, Pedro J.; Lugo-Viña, Eduardo; Méndez Torregrosa, Luis A.